Investigation into energy consumption, surface roughness and material removal rate of cylindrical components machined using wire electrical discharge turning process. (1st January 2013) - Giridharan, Abimannan; Samuel, G.L.
In this paper, the effect of input parameters such as pulse off time, servo feed and spindle rotation on energy consumption, surface roughness and material removal rate (MRR) of machined components are analysed during wire electrical discharge turning (WEDT) process. The parameters were varied at three levels and experiments were conducted using full factorial design. The energy consumption is measured using the power pulse train which is obtained from voltage and current pulse trains. It is observed that the pulse off time has significant effect on energy consumption and surface roughness is affected by the spindle rotation. It is also observed that material removal rate is affected by the energy dissipated during machining.